The oral histone deacetylase inhibitor LBH589 is a potential and promising therapeutic agent in multiple myeloma after at least two lines of chemotherapy including bortezomib or lenalidomide - Schmitt, Stefan; Ho, Anthony Dick; Goldschmidt, Hartmut (Onkologie, 2010)
Multiple myeloma as the second most common hematological malignancy is characterized by proliferation of monoclonal plasma cells. This entity still remains a non-curable disorder leading, amongst others, to complications as myeloma bone disease, bleeding events, kidney failure and neurological impairment. LBH589 is a histone deacetylase inhibitor with an epigenetic mechanism of action and the potential for treatment in myeloma. We report here about the successful treatment of a 44-year-old woman suffering from progressive myeloma with LBH589 after five different chemotherapies. During the 9 years after first diagnosis of myeloma in April 2000, our patient twice underwent an autologous stem cell transplantation and was also treated with the new substances bortezomib, thalidomide and lenalidomide.
Gesehen am 14.06.2023